2001
DOI: 10.1159/000055749
|View full text |Cite
|
Sign up to set email alerts
|

Distant Metastases from Thyroid and Parathyroid Cancer

Abstract: Thyroid cancer represents a unique biological tumor where even with the high incidence of distant metastases, the overall prognosis is not as poor as many other human cancers. The overall long-term survival in patients presenting initially with distant metastasis is approximately 50%. The overall incidence of distant metastases varies between 10 and 35%, depending upon the histology. The overall incidence is directly related to various histologies – being least in papillary thyroid carcinoma (10%) and highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 23 publications
(23 reference statements)
2
83
0
1
Order By: Relevance
“…The majority of thyroid cancers are localized at the time of diagnosis with only a small proportion (10-35%), depending on the histology, presenting with distant metastasis (7,8). This proportion is only 4-15% in the case of differentiated thyroid cancers (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of thyroid cancers are localized at the time of diagnosis with only a small proportion (10-35%), depending on the histology, presenting with distant metastasis (7,8). This proportion is only 4-15% in the case of differentiated thyroid cancers (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…This proportion is only 4-15% in the case of differentiated thyroid cancers (7,8). Common sites of metastasis include the lungs and bones (8)(9)(10)(11), while soft tissue metastasis is reportedly extremely rare (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Shaha et al have shown that there are several differences between HCC and follicular thyroid carcinoma 43 .…”
Section: Methodsmentioning
confidence: 99%
“…PTC is often multifocal and metastasizes to regional lymph nodes in about 40% of cases. Common sites of distant metastases from PTC are lung (49%), bone (25%), both lung and bone (15%), and central nervous system (12%) [2]. Other unusual sites of distant metastasis are the liver, kidneys and adrenal glands [3].…”
Section: Introductionmentioning
confidence: 99%